The Central Scotia Sea Floor – Palaeo-Oceanic Plate, Young Riftogenous Plate or Palaeo-Land Scotia? - Schenke, H.W.; Udintsev, G.B. (Український антарктичний журнал, 2009)
Although the bathymetry and geophysics of the Scotia Sea basin is rather well studied in general and is discussed in many publications there are still remaining questions about tectonics of its Central Part. In the western part of the Sea tectonic nature is well demonstrated by West rifted ridge and in the eastern part by East back-arc rift. The floor of the central part does not show such well expressed tectonic features. The usual interpretation of that part of basin floor is described as introduced fragment of the Pacific paleo-Plate or as newly created oceanic plate resulted by supposed rifting. Recent bathymetry and other geophysics survey is complemented with geological sampling lead to hypothesis on the existence there of a large relict of continental bridge between South America and West Antarctica. Хотя рельеф дна и геофизические параметры ложа котловины моря Скоша в общем изучены довольно хорошо и рассматривались во многих публикациях, всё же до сих пор остаются вопросы о тектонике центральной части ложа этой котловины. Тектоническая природа западной части дна моря Скоша хорошо демонстрируется Западным рифтогенным хребтом, а в восточной части – Восточным задуговым рифтом. Центральная часть ложа котловины обычно интерпретируется как внедрённый фрагмент Тихоокеанской плиты или как заново созданная океаническая плита, результатпредполагаемого рифтогенеза. Новейшие исследования рельефа дна и другие геофизические съёмки в сочетании со сбором геологических образцов приводят к предположению о существовании там большого реликта континентального моста между Южной Америкой и Западной Антарктидой – палео-Земли Скоша. Хоча рельєф дна і геофізичні параметри ложа котловини моря Скоша загалом вивчені досить добре і роглядалися в багатьох публікаціях, усе ж таки й досі залишаються питання щодо тектоніки центральної частини ложа цієї котловини. Тектонічна частина природи західної частини дна моря Скоша добре демонструється Західним рифтогенним хребтом, а у східній частині – Східним задуговим рифтом. Центральна частина ложа котловини зазвичай інтерпретується як упроваджений фрагмент Тихоокеанської плити або як заново створена океанічна плита, результат гаданого рифтогенезу. Найновіші дослідження рельєфу дна та інші геофізичні зйомки у сполученні зі збиранням геологічних зразків приводять до припущень про існування там великого релікту континентального моста поміж Південною Америкою і Західною Антарктидою – палео-Землі Скоша.